Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/infdis/jir172
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Sparing H5N1 A/Indonesia/05/2005 Pre-pandemic Influenza Vaccine in Adults and Elderly Adults: A Phase III, Placebo-Controlled, Randomized Study

Abstract: Background. Highly pathogenic avian influenza H5N1 viruses remain a threat to human health, with potential to become pandemic agents.Methods. This phase III, placebo-controlled, observer-blinded study evaluated the immunogenicity, cross-reactivity, safety, and lot consistency of 2 doses of oil-in-water (AS03A) adjuvanted H5N1 A/Indonesia/05/2005 (3.75 μg hemagglutinin antigen) prepandemic candidate vaccine in 4561 adults aged 18–91 years.Results. Humoral antibody responses in the H5N1 vaccine groups fulfilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…Indeed, the AS03 adjuvant present in some vaccines promotes immunogenicity by modulating the expression of local cytokines and by increasing the antigen loading in monocytes (17). Although this adjuvant has been safely administered with the H1N1 and the H5N1 strains to thousands of healthy adults (18), more data are needed about the potential for allosensitization among patients with renal disease. Indeed, many reports show that de novo occurrence of posttransplant anti-HLA Abs is associated with chronic rejection and graft loss (19 -21).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the AS03 adjuvant present in some vaccines promotes immunogenicity by modulating the expression of local cytokines and by increasing the antigen loading in monocytes (17). Although this adjuvant has been safely administered with the H1N1 and the H5N1 strains to thousands of healthy adults (18), more data are needed about the potential for allosensitization among patients with renal disease. Indeed, many reports show that de novo occurrence of posttransplant anti-HLA Abs is associated with chronic rejection and graft loss (19 -21).…”
Section: Introductionmentioning
confidence: 99%
“…Other trials have reported a low incidence of adverse effects (0%-3%) and no significant difference in serious adverse events between influenza vaccine and placebo. [15][16][17] Of the RCTs, FLUCAD 31 was likely the most well designed. The authors attempted to minimize bias and confounding through appropriate randomization, use of intention-to-treat analyses, and minimal loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, in prospective randomized trials that included CV outcomes for safety assessment, influenza vaccination was not associated with a reduction in CV events, [15][16][17][18] although these trials were limited by low event rates and potential for misclassification. 19 Both the American Heart Association/American College of Cardiology and the European Society of Cardiology recommend the influenza vaccine annually for individuals with established CVD [20][21][22] without specifically stating that the purpose is to reduce the risk of CV events.…”
Section: Introductionmentioning
confidence: 99%
“…6,[10][11][12] The pandemic experience created the unusual situation in which much of what we know about the immunological impact of AS03 is derived from human studies. This body of work has demonstrated that AS03-adjuvanted, dose-sparing formulations can induce strong serum antibody responses that persist for at least 12 months in healthy children, [13][14][15][16][17] adults [18][19][20][21][22][23] and the elderly, [24][25][26] and that influenza-specific, poly-functional CD4C T cells can be detected in human PBMC samples for at least 6 months after vaccination. [27][28][29] We have previously shown that AS03 can induce powerful humoral 6,12 and cellular responses 6 to influenza antigens over a surprisingly wide range of Ag doses (100-to 1000-fold lower than a 'standard' 3 mg HA dose in mice) at 3 weeks after a booster immunization The objective of this study was to determine the persistence of these responses up to 34 weeks after LD-AS03-adjuvanted vs. HD-unadjuvanted vaccination.…”
Section: Discussionmentioning
confidence: 99%